THE CONSULTING AS A LEARNING OPPORTUNITY FOR NONGOVERNMENTAL ORGANIZATIONS: A STUDY IN THE CITY OF RECIFE / PE - Correia, Fernanda Bruto da Costa; Feitosa, Marcos Gilson Gomes; Vieira, Naldeir dos Santos (Revista de Administração da UFSM, 2010)
Non-governmental organizations (NGOs) are active and growing institutions throughout the country, being from the 90s, to suit the environmental contingencies, are starting to professionalize, adopting administrative practices, such as management and evaluation of the impacts of their projects. Thus, part of NGOs started to hire professionals who act as consultants, which are organizational and specialists. In face of the above, the objective was to identify and analyze the learning, which are related to the practice of hiring consultants, obtained by NGOs. For both, there were semi-structured interviews with managers of NGOs that operate in the metropolitan area of Recife / EP and its contracted services of consultants. It appears that NGOs, with the hiring of consultants, learned that it is necessary that these professionals know and have experience of working in social organizations, who understand their specificities and to adopt a methodology which establishes a reflective learning, being regarded as ineffective those who only deploy “packages” managerial pre-prepared.